Rising mortality in patients with combined burn and trauma. Issue 8 (December 2018) - Grigorian, Areg; Nahmias, Jeffry; Schubl, Sebastian; Gabriel, Viktor; Bernal, Nicole; Joe, Victor
Highlights: Mortality has increased is certain groups of patients with combined burn-traumas. An increased %TBSA increases risk of death in all combined burn-traumas. In TBSA > 20%, the severity of combined trauma is not a risk factor for mortality. Abstract: Combined trauma in the burn patient has been previously shown to have higher mortality. With improved critical care and multidisciplinary approach, we hypothesized the risk of mortality in combined burn and trauma has decreased. A retrospective analysis of trauma, burn and combined burn-trauma patients in the National Trauma Data Bank was performed comparing years 2007–2015 to years 1994–2002. The impact of burn injuries on mortality in patients with minor trauma has decreased (OR 2.45, CI 2.26–2.66, p < 0.001 compared to OR 4.04, CI 4.51–4.66, p < 0.001) in years 2007–2015 while the impact of burn injuries on mortality in patients with severe trauma has increased (OR 1.37, CI 1.29–1.47, p < 0.001 compared to OR 1.26, CI 1.05–1.51, p < 0.001). When controlling for known risk factors of mortality in burn and trauma, the contribution of the severity of trauma on mortality in combined burn-trauma patients with total body surface area ≥20% is negligible. In contrast, an increase in percentage of total body surface area burned is associated with a step-wise increase in mortality for all combined burn-trauma patients. However, the largest impact is seen in patients with minor trauma. This population represents a unique overlap of patients where future collaborative research can help identify best practices and improve outcomes.